2017
DOI: 10.3390/en10070850
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Production of Fuel Briquettes Made from Biomass and Plastic Wastes

Abstract: Abstract:In this study, the physical properties of briquettes produced from two different biomass feedstocks (sawdust and date palm trunk) and different plastic wastes, without using any external binding agent, were investigated. The biomass feedstocks were blended with different ratios of two waste from electrical and electronic equipment (WEEE) plastics (halogen-free wire and printed circuit boards (PCBs)) and automotive shredder residues (ASR). The briquettes production is studied at different waste proport… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 38 publications
0
12
0
2
Order By: Relevance
“…Corn husks, cobs and straw were mixed with other biomass, such as cassava husk [28] and oil palm husk [29]. In addition, some works also incorporated plastic waste associated with other materials in the composition of their briquettes, such as sawdust, date palm trunk and even sub-bituminous coal (non-renewable coal) [30,31].…”
Section: Briquetting 21 Biomass and Pre-treatments Used In The Production Of Briquettesmentioning
confidence: 99%
See 2 more Smart Citations
“…Corn husks, cobs and straw were mixed with other biomass, such as cassava husk [28] and oil palm husk [29]. In addition, some works also incorporated plastic waste associated with other materials in the composition of their briquettes, such as sawdust, date palm trunk and even sub-bituminous coal (non-renewable coal) [30,31].…”
Section: Briquetting 21 Biomass and Pre-treatments Used In The Production Of Briquettesmentioning
confidence: 99%
“…The studies that kept this parameter fixed did not have their values highlighted in Table 3. Among the works cited, only Garrido, Conesa and Garcia [30] explored this variable at different levels. Heating at 120 and 130 • C was carried out only on briquettes that did not compact at room temperature.…”
Section: Effect Of Temperature On the Production Of Briquettesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a significant decrease of the mechanical durability index for a larger fraction was observed, the Du values can be considered satisfactory. The research of other authors showed that briquettes made of plant materials should be characterized by the higher mechanical durability index Du, exceeding 80% [42][43][44]. However, these values are not always achieved.…”
Section: The Mechanical Durability Index-pn-en Iso 17831-2: 2016-02 Standardmentioning
confidence: 97%
“…To make the molding block, first, the CR must be ground to specific particle size. At the same time, humidity control and adding adhesives should also be emphasized [66,67].…”
Section: The Cr Briquette Fuel Projectmentioning
confidence: 99%